"A Statistically Representative Climate Change Debate": Satirical Television News, Scientific Consensus, and Public Perceptions of Global Warming. Issue 3 (27th May 2017) - Brewer, Paul R.; McKnight, Jessica
ABSTRACT: Satirical television news programs provide the public with potential sources of information about climate change. This study uses a segment from Last Week Tonight with John Oliver as a test case for exploring how coverage from such programs that features consensus messaging may influence viewers' perceptions of global warming. The segment presents a "statistically representative climate change debate" to affirm the scientific consensus on anthropogenic climate change and satirize television news coverage "balancing" this consensus with skeptics' arguments. Results from a randomized experiment demonstrate that watching the segment increased viewers' own belief in global warming, as well as viewers' perceptions that most scientists believe in global warming. The latter effect was stronger among participants with low interest in the environment and global warming than among those with high interest. The segment's impact on perceptions of scientists' views may have mediated its effects on viewers' own beliefs about global warming.